Respuesta :

Answer:

g (h (x) ) = 5/8

Step-by-step explanation:

We are given the following two functions and we are to find the value of [tex] g ( h ( - 3 ) ) [/tex]:

[tex] g ( x ) = \frac { x + 1 } { x + 2 } [/tex]

[tex] h ( x ) = 4 - x [/tex]

Firstly, we need to find the function :

[tex] g ( h ( x ) ) = \frac { ( 4 - x + 1 ) } { ( 4 - x - 2 ) } = \frac { 5 - x } { 2 - x } [/tex]

Now substituting the value [tex]x=-3[/tex] in it:

[tex] g ( h ( x ) ) = \frac { 5 - (-3) } { 2 - (-3) }  [/tex]

g (h (x) ) = 5/8

ACCESS MORE